DEVELOP THE MUSICAL THINKING OF THEIR STUDENTS BY TEACHING MUSICAL LITERACY - M.Djumabayeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article examines the study of musical literacy in the learning process and its role in the formation of musical thinking among students.